Women's views on content and delivery methods for interventions to improve preconception health: a qualitative exploration - Michael P. Daly; Ruth R. Kipping; James White; Julia Sanders (Frontiers Media S.A., 2024)
BackgroundSystematic review evidence suggests preconception health interventions may be effective in improving a range of outcomes. However, few studies have explored women's views on potential content and delivery methods for these interventions.MethodsParticipants were purposively sampled from respondents (n = 313) of a survey. Semi-structured, in-depth interviews were conducted to explore their views on seven candidate delivery methods for preconception health interventions: general practitioners (GPs), nurse practitioners, pharmacists, social media, personal texts and emails, pregnancy tests, and health education in schools. Data were analyzed using a data-driven framework analysis.ResultsTwenty women were interviewed. Women wanted interventions to be easily accessible but allow them to conceal their pregnancy plans. They preferred to choose to receive preconception interventions but were receptive to health professionals raising preconception health during 'relevant' appointments such as contraceptive counseling and cervical smear tests. They wanted intervention content to provide trustworthy and positively framed information that highlights the benefits of good preconception health and avoids stigmatizing women for their weight and preconception actions. The inclusion of support for preconception mental health and the use of visual media, personalization, simple information, and interesting and unfamiliar facts were viewed favorably.ConclusionInterventions to improve preconception health should reflect the sensitivities of pregnancy intentions, be easy to access in a way that enables discretion, and be designed to seek consent to receive the intervention. These interventions should ideally be tailored to their target populations and provide trustworthy information from reputable sources. The potential for unintended harmful effects should be explored.